Highly selective aqueous phase hydrogenation of phenols over nanostructured RuO2 on MCM-41 catalysts - Betsy, K. J.; Lazar, Anish; Vinod, C. P. (Nano-Structures & Nano-Objects, 2018)
Selective aqueous phase hydrogenation of phenol as well as its derivatives is important for the synthesis of chemical intermediates which are crucial for the manufacture of high-tonnage commodities and a multitude of value added platform chemicals. Herein, we report a facile catalyst made of highly dispersed small RuO2 nanoparticles supported on mesoporous MCM-41 using one-pot approach. The optimal 5RuO2-MCM-41 catalyst with particle size 6-8 nm showed excellent activity and selectivity in aqueous phase hydrogenation of phenol and other functionalized substrates, which are building blocks of lignin, to corresponding cyclohexanol products without any additives. These catalysts showed better stability and can be reused several times without any significant drop in activity which proves the heterogeneity of the immobilized oxide catalyst.

Hydrogenation of levulinic acid to gamma-valerolactone over nickel supported organoclay catalyst - Kamble, Paresh A.; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (Catalysis Today, 2023)
In this work, a series of Ni/Organoclay catalysts with different Nickel loadings were prepared by the wetimpregnation method for the catalytic hydrogenation of levulinic acid (LA) to gamma-valerolactone (GVL). Reaction parameters such as reaction temperature, pressure, solvent effect, and wt% of catalyst were optimized to get excellent conversion of levulinic acid selectively to gamma-valerolactone. Ni/Organoclay with 30% Nickel loading exhibited 100% conversion of LA with 100% selectivity towards GVL at 140 degrees C and 3.0 MPa H2 pressure using 1,4-dioxane as a solvent in 5 h. Different bulk and surface characterization techniques such as XRD, BET, FE-SEM, HR-TEM, XPS, XRF, NH3-TPD, and H2-Chemisorption were used to characterize the Ni/Organoclay catalyst. BET and NH3-TPD analysis showed that the pre-treatment of bentonite with surfactant (CTAB) improved the pore volume, surface area, and acidity of Organoclay which assisted in improving the conversion and selectivity of LA and GVL respectively.
Keywords: ?-Valerolactone (GVL); Bentonite; Hydrogenation; Levulinic acid (LA); Nickel; organoclay

Hydrogenation of furfural to tetrahydrofurfuryl alcohol over nickel-supported on organoclay catalyst - Kamble, Paresh A.; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (Applied Catalysis A-General, 2024)
Nickel supported on organoclay prepared by the impregnation method provides excellent catalytic activity for the hydrogenation of furfural to tetrahydrofurfuryl alcohol. The relative amount of metal and acidic sites influences the hydrogenation reaction. Additionally, by varying the temperature and the H-2 pressure, we can regulate the interaction of furfural with the active sites. And this may decide the fate of the reaction whether it will undergo a two-step hydrogenation to form tetrahydrofurfuryl alcohol or a rearrangement reaction to form cyclopentanone/cyclopentanol. Water was found to be the best solvent for the selective formation of tetrahydrofurfuryl alcohol. Even though alcohols inhibited rearrangement reaction, the hydrogenation of furfural was more selective towards furfuryl alcohol. Ni/O-clay30A under the optimum conditions of 120 degrees C, 4.0 MPa, and in 1 h offered complete conversion of furfural to tetrahydrofurfuryl alcohol.
Keywords: furfural; Hydrogenation; Nickel; organoclay; Tetrahydrofurfuryl alcohol

Hot injection assisted electronically modulated twin and grain boundary rich sub-2 nm pt3co alloy resistant to phosphate ion for PEMFCs - Singh, Mayank U.; Jadhav, Swapnil D.; Shivankar, Bhavana R.; Pandikassala, Ajmal; Kumar, Yogesh; Krishnamurty, Sailaja; Vinod, C. P.; Kurungot, Sreekumar (Small, 2025)
Modulation of the electronic d-band center, structural defects (line defects), and particle size of Pt3Co alloy electrocatalyst have huge significance in elevating its electrochemical oxygen reduction reaction activity. Deviating from traditional high-temperature strategies, the current work focuses on ripening these benefits by implying a simple economically viable hot-injection-assisted modified polyol process. A conclusive control over decrementing particle size starting from 2.7 to 1.3 nm, an increasing degree of strain (twin boundary), and shifting of the d-band center away from the Fermi level are obtained via varying the temperature to which the solution is injected. The catalyst prepared via the injection at 200 degrees C (Pt3Co(1.3 t,g-b)/fVC-200) has delivered an electrochemical surface area of 84 m(2) g(Pt)(-1) with the onset and half-wave potentials of 0.980 and 0.858 V, respectively, versus RHE and a limiting current of -6.0 mA cm(-2) with stability till 20k cycles. In the high-temperature proton exchange membrane fuel cell Pt3Co(1.3 t,g-b)/fVC-200-based cell has outperformed Pt/C rendering 600 mWcm(-2) under H-2-Air compared to 529 mWcm(-2) of Pt/C with 20% lower Pt loading and double the stability due to enhanced resistance toward phosphoric acid for accelerated voltage cycling. A similar enhancement is seen while employing the catalyst for low-temperature fuel cells.
Keywords: electrocatalyst; grain boundary; hot injection synthesis; modified polyol process; oxygen reduction reaction; proton exchange membrane fuel cell; Pt3Co alloy; twin boundary; valance band X-ray photoelectron spectroscopy

Hydrogenation of CO2 catalyzed by thermally decomposed cobalt-containing alkaline earth metal carbonates - Gupta, Sharad; Vinod, C. P.; Poupin, Christophe; Jagadeesan, Dinesh (Energy & Fuels, 2025)
CO2 hydrogenation over Co catalysts supported on alkaline earth metal oxides was investigated. The catalysts were prepared by thermally decomposing alkaline metal carbonates CoMCO3, where M = Mg, Ca, Sr, and Ba, in H2. During the thermal activation, contingent upon the thermal stability of the precursor, it transformed into a composite of metal oxides, metals, and undecomposed metal carbonates. The thermal activation temperature, the ratio of CO2 to H2, the composition, and the basicity of the catalyst all played a significant role in influencing the conversion of CO2 and the selectivity to CH4. Among the various Co-containing alkaline earth metal carbonate precursors, CoCaCO3 activated at 400 degrees C yielded the highest steady-state CO2 conversion of 54% with a CH4 selectivity of 89.8% throughout 28 h in the reaction stream containing a 1:4 ratio of CO2 and H2. Detailed characterization showed that the CaCo-400 catalyst contained metallic Co, CaO, and undecomposed CaCO3 phases. The study assumes significance in understanding the role of the composition of catalysts in the formation of CO2 hydrogenation.